Protection Against Post-resuscitation Acute Kidney Injury by N-Acetylcysteine via Activation of the Nrf2/HO-1 Pathway - Wang, Shiwei; Liu, Guoxiang; Jia, Tianyuan; Wang, Changsheng; Lu, Xiaoye; Tian, Lei; Yang, Qian; Zhu, Changqing (Frontiers in Medicine, 2022)
Background and Objective Acute kidney injury (AKI), the common complication after cardiopulmonary resuscitation (CPR), seriously affects the prognosis of cardiac arrest (CA) patients. However, there are limited studies on post-resuscitation AKI. In addition, it has been demonstrated that N-acetylcysteine (N-AC) as an ROS scavenger, has multiorgan-protective effects on systemic and regional ischaemia-reperfusion injuries. However, no studies have reported its protective effects against post-resuscitation AKI and potential mechanisms. This study aimed to clarify the protective effects of N-AC on post-resuscitation AKI and investigate whether its potential mechanism was mediated by activating Nrf-2/HO-1 pathway in the kidney. Methods We established cardiac arrest models in rats. All animals were divided into four groups: the sham, control, N-AC, and ZnPP groups. Animals in each group except for the ZnPP group were assigned into two subgroups based on the survival time: 6 h and 48 h. The rats in the control, N-AC, and ZnPP groups underwent induction of ventricular fibrillation (VF), 8 minutes untreated VF and cardiopulmonary resuscitation. Renal function indicators, were detected using commercial kits. Renal pathologic changes were assessed by haematoxylin–eosin (HE) staining. Oxidative stress and inflammatory responses were measured using the corresponding indicators. Apoptosis was evaluated using terminal uridine nick-end labelling (TUNEL) staining, and expression of proteins associated with apoptosis and the Nrf-2/HO-1 pathway was measured by western blotting. Results N-AC inhibited post-resuscitation AKI. We observed that N-AC reduced the levels of biomarkers of renal function derangement; improved renal pathological changes; and suppressed apoptosis, oxidative stress, and inflammatory response. Additionally, the production of ROS in the kidneys markedly decreased by N-AC. More importantly, compared with the control group, N-AC further upregulated the expression of nuclear Nrf2 and endogenous HO-1 in N-AC group. However, N-AC-determined protective effects on post-resuscitation AKI were markedly reversed after pretreatment of the HO-1 inhibitor zinc protoporphyrin (ZnPP). Conclusions N-AC alleviated renal dysfunction and prolonged survival in animal models of CA. N-AC partially exerts beneficial renal protection via activation of the Nrf-2/HO-1 pathway. Altogether, all these findings indicated that N-AC as a common clinical agent, may have the potentially clinical utility to improve patients the outcomes in cardiac arrest.